Carbon coated chevrel phase of Mo6S8 as anode material for improving electrochemical properties of aqueous lithium-ion batteries. (20th December 2017) - Chu, Haomiao; Pan, Junli; Bai, Shouli; Ma, Yaqiang; Feng, Yongjun; Wen, Yuehua; Yang, Yusheng; Luo, Ruixian; Chen, Aifan
Abstract: The carbon-coated chevrel phase of Mo6 S8 as electrode material was fabricated for the first time. Compared with the bare Mo6 S8 and 10%C-Mo6 S8 anodes, the 5%C-Mo6 S8 anode possesses excellent rate capability and cyclic performance at the cutoff voltage of 1.5 V using LiMn2 O4 as the cathode, which delivers a reversible capacity of ∼ 85 mAh·g −1 and an average discharge voltage of as high as ∼ 2 V maintains 93% of initial discharge capacity even after 400 cycles at 1C and in 21 M aqueous electrolyte. This study provides a promising anode material for aqueous lithium-ion batteries because of its high capacity, stability and environmental inertness. Furthermore, the results demonstrate that this method could expand the synthesis and application of these unique compounds. Graphical abstract: Highlights: Covering the carbon layer in situ on the surface of Mo6 S8 is firstly synthetized. Effects of the carbon coating Mo6 S8 on electrochemical properties are discussed. The as synthesized 5%C-coated Mo6 S8 has smaller particle size and porous structure. 5%C-Mo6 S8 anode possesses excellent rate capability and cyclic performance.